Berseem Clover (Trifolium Alexandrinum L.) Seed Yield and Seed Quality Response to Irrigation Frequency and Foliar Spray of Plant Bio-Regulators - Ghimire, Ram Prasad; Devkota, Naba Raj; Devkota, Durga; Sharma, Mohan Prasad (SAARC Journal of Agriculture, 2023)
The primary challenges in Berseem clover (Trifolium alexandrinum L.) seed production in Nepal are low productivity levels and substandard quality indicators. To address this issue, the experiments were conducted at the Regional Agricultural Research Station, Khajura, Banke, Nepal, and replicated in farmers' fields using a Randomized Complete Block Design from November 2018 to June 2019. Four irrigation schemes and three levels of foliar sprays of plant bio-regulators were used. The experiment result revealed that three and four irrigations were most suitable for achieving higher seed yield (p<0.05), resulting in 0.99 and 0.93 t ha-1 at on-station and 0.87 and 0.85 t ha-1 at on-farm, respectively. Similarly, two and three sprays of plant bio-regulators yielded better (p<0.05) seed yields of 0.89 and 0.94 t ha-1 at on-station and 0.79 and 0.85 t ha-1 at on-farm, respectively, without significant alteration on days taken to seed maturity and biological yield. The interactions between the levels of irrigation and plant bio-regulators spray were non-significant (p>0.05) for seed yield and biological yield. The experiments demonstrated that three irrigations @ 666.67 kiloliters of water ha-1 at 15-day intervals after one cut at 60 days after sowing, and three foliar sprays of plant bio-regulators (P2O5 @ 2 kg ha-1 + KNO3 @ 4 kg ha-1) at 7-day intervals in the pre-flowering stage, significantly enhanced the seed yield and quality of Berseem clover. SAARC J. Agric., 21(2): 131-143 (2023)